ANALISIS SISTEM INFORMASI AKUNTANSI PENJUALAN DALAM MENINGKATKAN PENGENDALIAN INTERNAL PADA PT. ANUGERAH PERKASA SEJAHTERA - Lase, Popi Terima Jaya; Susanthi, Putu Rani (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
This study aims to find out how the analysis of sales accounting information systems in improving internal control at PT. Anugerah Perkasa Sejahtera. This research was conducted at PT. Anugerah Perkasa Sejahtera using a descriptive qualitative method, namely explaining the sales accounting information system in improving internal control. The results of this study indicate (1) the organizational structure at PT. Anugerah Perkasa Sejahtera actually exists but has not been made in a structured manner or chart, (2) Approval in adding credit notes is approved by the salesman, (3) The existence of uncollectible accounts due to customer problems in payment, and (4) There is rejection of ordered goods due to discrepancies with customer orders.